Democracy in Modern Iran : Islam, Culture, and Political Change. - Mirsepassi, Ali (NYU Press, 2010)
Can Islamic societies embrace democracy? In Democracy in Modern Iran, Ali Mirsepassi maintains that it is possible, demonstrating that Islam is not inherently hostile to the idea of democracy. Rather, he provides new perspective on how such a political and social transformation could take place, arguing that the key to understanding the integration of Islam and democracy lies in concrete social institutions rather than pre-conceived ideas, the every day experiences rather than abstract theories. Mirsepassi, an Iranian native, provides a rare inside look into the country, offering a deep under.